2013
DOI: 10.1097/phm.0b013e31825f148a
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood–Derived Mesenchymal Stem Cells in the Cultured Rabbit Intervertebral Disc

Abstract: Objective Back pain associated with symptomatic disc degeneration is a common clinical condition. Intervertebral disc (IVD) cell apoptosis and senescence increase with aging and degeneration. Repopulating the IVD with cells that could produce and maintain extracellular matrix would be an alternative therapy to surgery. The objective of this study was to determine the potential of human umbilical cord blood–derived mesenchymal stem cells (hUCB-MSCs) as a novel cell source for disc repair. In this study, we inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…Allogeneic cells could be isolated from umbilical cord blood,(22) umbilical tissue,(23) or articular surface. (24, 25) Allogeneic cells from younger donors have higher expansion potential than most autologous cells.…”
Section: Cell Sources and Typesmentioning
confidence: 99%
“…Allogeneic cells could be isolated from umbilical cord blood,(22) umbilical tissue,(23) or articular surface. (24, 25) Allogeneic cells from younger donors have higher expansion potential than most autologous cells.…”
Section: Cell Sources and Typesmentioning
confidence: 99%
“…UCB-derived MSCs have also demonstrated promise in xenogeneic mouse models of liver injury [23] and islet regeneration in type 1 diabetes [24]. Preclinical studies in a rabbit model of intervertebral disc degeneration showed improvement using UCB-derived MSCs that could differentiate into chondrocyte-like cells [25]. Another study using larger animal models addressed the use of equine UCB-derived MSCs for immune modulation in horses [26].…”
Section: Mscsmentioning
confidence: 98%
“…Other types of stem cells, such as human amnion epithelial cells (hAECs) derived from amniotic tissue, and stem cells obtained from human umbilical cord blood or tissue, are also being used xenogeneically in preclinical studies of the treatment of lumbar spinal degenerative conditions [5,53]. The ready availability of such cells, derived from discarded pregnancy tissues and thus without ethical constraints, and the development of large cell banks to store such cells may make them a convenient source of stem cells for use in degenerative spinal applications, should preclinical efficacy be demonstrated.…”
Section: Types Of Stem Cells and Cell-based Therapiesmentioning
confidence: 99%